Effect of time to pre‐emptive transjugular intrahepatic portosystemic shunt on patient outcome, a UK multicentre cohort study. Issue 2 (18th October 2022) - Dunne, Philip; Finkel, Jemima; Khan, Faisal; Lachlan, Neil; Patch, David; Tripathi, Dhiraj; Stanley, Adrian; Hayes, Peter
Summary: Background: Pre‐emptive transjugular intrahepatic portosystemic shunt (pTIPSS) should be considered within 72 hours following acute oesophageal variceal bleeding. However, recent studies highlight the difficulty in providing pTIPSS within this narrow timeframe. Delaying pTIPSS beyond 72 hours has not been studied. Aim: To determine if the time taken to perform pTIPSS alters patient outcome. Method: Patients referred to 4 UK tertiary centres for pTIPSS between 01 January 2010 and 31 December 2018 were included. Time from endoscopy to pTIPSS was recorded and pre‐defined clinically relevant outcomes were observed relative to two groups: early pTIPSS (<72 h) and late pTIPSS (72 h–28 days). The primary outcome was transplant‐free survival at 1‐year. Follow‐up was until 31 December 2020. Results: A total of 83 patients received early pTIPSS and 88 received late pTIPSS. Baseline characteristics were similar with no requirement for propensity score‐matched analysis. There was no difference between early and late pTIPSS groups for patient outcomes; 1‐year transplant‐free survival rate (69.9% vs 71.6%, p  = 0.73, HR 0.91, 95% CI 0.52–1.58), long‐term survival ( p  = 0.52, HR 1.132, 95% CI 0.77–1.65), variceal rebleeding (4.82% vs 11.36%, p  = 0.09, HR 0.411, 95% CI 0.14–1.17), hepatic encephalopathy (43.93% vs 34.61%, p  = 0.26) and new or worsening ascites (16.6% vs 13.46%, p  = 0.79). Death due to liver failure was significantly more prevalent in those undergoing early pTIPSS compared to late pTIPSS (44% vs 16%, p  = 0.046, HR 2.79, 95%CI 1.02–8.32). Conclusion: Placement of pTIPSS within 72 hours offered similar short‐ and long‐term survival benefits compared to pTIPSS placed between 72 hours and 28 days. Early pTIPSS may be associated with an increased risk of liver failure‐related mortality. Further large, randomised studies are required to evaluate these findings. Abstract : Pre‐emptive TIPSS is recommended <72hrs following endoscopy for variceal bleeding. This timeframe is based on historic data. We found that survival rates were unaltered by timeframe, between 2 groups: "early pTIPSS" (<72hrs) and "late pTIPSS" (72hrs–28 days).